The Effectiveness of Prenatal Yoga on Back Pain Intensity of Third Trimester Pregnant Women in Surakarta - Nindi Oktavia; Ardhia Putri Pramesti; Rizka Ayu Setyani (Journal of Community Empowerment for Health, 2023)
The third trimester is the period of pregnancy in the last three months of pregnancy. The adaptation process that occurs during pregnancy often causes discomfort for pregnant women, so it is necessary to do several things from prevention to treatment. The most common discomfort for pregnant women is back pain. Pregnant women can experience back pain due to increased weight and spine. overcome back pain by massaging the back but it is not effective and prenatal yoga has never been done to treat back pain in the interviewed third-trimester pregnant women. The purpose of this study was to assess the effectiveness of prenatal yoga on back pain in third-trimester pregnant women. This study was a quasi-experimental design with a pre-post test control group design. The sampling technique in this study was purposive. In the implementation of this research respondents obtained as many as 30 respondents. after prenatal yoga in the third-trimester pregnant women is 2.07 with a standard deviation of 0.799. The results showed that there was an effect of prenatal yoga on the level of back pain in the intervention group before and after prenatal yoga was performed in the third trimester of pregnant women in Surakarta City in 2022 with a p-value of 0.001 (p > 0.05). The reduction in back pain was highest in the intervention group because the intervention group was given prenatal yoga. Prenatal yoga affected decreasing the level of back pain in third-trimester pregnant women. Researchers recommend prenatal yoga as physical exercise for pregnant women